Small Bowel Obstruction Caused by Spontaneous Transomental Hernia: A Case Report - So Ra Ahn; Keun Young Kim; Joo Hyun Lee (The Korean Journal of Gastroenterology, 2022)
An internal hernia is a protrusion of visceral contents through a defect in the mesentery or peritoneum. Small bowel obstruction is a common clinical presentation of internal hernias, accounting for 4.1% of all intestinal obstructions. Transomental hernia is a rare type of internal hernia (1-4% of internal hernias), with non-specific symptoms, making its preoperative diagnosis difficult. It is strangulated more frequently, and the postoperative mortality rate is high (30%). Therefore, early diagnosis and management are crucial. We report a case of a 77-year-old female who presented with small bowel obstruction, and a suspected incarcerated internal hernia on abdomen-pelvis CT. A spontaneous transomental hernia was confirmed on emergency laparotomy.